STUDY OF CARDIOPROTECTIVE AND ANTI-ISCHEMIC EFFECTIVENESS OF STANDARD TREATMENT FOR ISCHEMIC HEART DISEASE WITH ADDITION OF PERINDOPRIL ARGININE, IN OLDER PATIENTS - L. F. Maksyutova; A. F. Maksyutova; G. M. Bikkinina (Российский кардиологический журнал)
Aim. To evaluate the cardioprotective, anti-ischemic and vasoprotective effectiveness of perindopril arginine (Prestarium А®, Les Laboratories Servier, France) in stable angina patients of older age, after myocardial infarction (MI).Material and methods. Totally, 68 patients of older age (72±12 y.) included, with stable angina, who had MI. All patients underwent echocardiography with dopplerographic analysis of transmitral blood flow, Holter monitoring of ECG, ultrasound dopplerography of carotid arteries. Patients from the 1 group (33 persons) were taking standard therapy of stable angina. Patients from the 2 group (n=35) as addition were taking PA 10 mg daily.Results. By the data of Holter ECG, in patients of both groups there was decrease of mean frequency of angina attacks (by 76,4% in 1 group, by 86,3% in 2), need for nitroglycerin use (by 68,7% and 71,3%, resp.), frequency of ischemia episodes (by 35,5% and 55,6%, resp.), total daily duration of ischemia (50,3% and 49,7%), depth of ischemic ST segment depression (44,6% and 58,6%, resp.). There was more prominent significant decrease of the parameters mentioned, in patients taking Prestarium А®. Also, in the 2 group patients the decrease of intima-media thickness of the right and left common carotid arteries was more significant than in the 1 group. In 2 group there was increase of relation of the peak velocities of the left ventricle (LV) filling in early phase of diastole and in atrium systole phase, by 14,6% and decrease of end-diastolic size of the LV by 10,9%.Conclusion. Usage of Prestarium А® in stable angina patients of older age, after MI, was effective, which presented with the decrease of the frequency and intensity of angina attacks, slowing of desadaptive LV remodeling processes, improvement of clinical condition, decrease of supraventricular rhythm disorders, positive influence on the heart and vessels, hence having vasoprotective and cardioprotective effect.